The Dynamics of Rasm Uthmani and Rasm Imla’i in the Qur’anic Mushaf: A Historical and Practical Study in Indonesia - Fariha Akmaliatu Sholihah; Ahmad Mustakim (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2025)
The writing of the Qur’anic manuscript has developed through two primary systems: Rasm Uthmani and Rasm Imla’i. In Indonesia, the dynamics between these two systems are evident in the processes of transmission, reception, and standardization of the Qur’anic script, influenced by historical developments and official policies, particularly from the Lajnah Pentashihan Mushaf al-Qur’an. This study aims to examine the transformation and adaptation of Qur’anic writing systems over time, as well as to analyze the impact of standardization policies on community practices. Using a historical-philosophical approach and a library research method, this study analyzes various manuscripts and printed mushafs. The findings indicate that Rasm Imla’i was more dominant during the early development of local mushafs due to limited access to the principles of Rasm Uthmani. However, since the implementation of standardization by religious authorities, Rasm Uthmani has become the official form in mushaf publication, although the Imla’i form continues to be used in educational contexts for pedagogical reasons. These findings reveal a tension between religious authority and local tradition and suggest the need for an epistemic re-evaluation of mushaf standardization policies within the context of contemporary Indonesia.